PENGARUH PAD, DAU DAN DAK TERHADAP BELANJA MODAL - Pradana, Yosea Eka; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
Local cash expenditureis meant to meet some programs and specific requirements in order to improvepublic services which have occured in the area.The local cash expenditureis known as regional expenditure andthere is capital expenditure in regional expenditure. According to the goverment accounting standard (SAP) thecapital expenditure is the expenditure which is made by the local government in order to form capital to addfixed assets or inventories that give benefit more than one accounting period, including the expenses formaintainance in which the characteristic is to maintain or to increase its useful life andto increase the capacityand the quality of the assets. This researchis aimed to find out the influence of local own source revenue (PAD),general allocation fund (DAK) to the capital expenditure in 6 (six) districts in the East Java, i.e.: Probolinggo,Lumajang, Jember, Bondowoso, Situbondo and Banyuwangi. The data is secondary data in 2009-2014 periodswhich has been issued by the Directorate General of Local Goverment Fiscal Balance of Financial Department.The data analysis technique has beendoneby usingquantitative analysis. The results of these research shows thatthe local own source revenue (PAD), general allocation fund (DAU) and special allocation fund (DAK) havesignificant influence in capital expenditure, but the general allocation fund,it hasnegative influence. Whenthegeneral allocation fund (DAU)is increasedthen the capital expenditures is decreased and vice versa.Keywords: Local own source revenue (PAD),general allocation fund (DAU), special allocation fund (DAK)capital expenditure.